Materials with Improved Heat Resistance Characteristics - Sirgiyevich, Rosilov Mansur; o‘g‘li, Qodirov Alibek Rauf (Research Parks Publishing LLC, 2023)
A production process has been developed and a scheme of a pilot plant for the production of oligomethyl-silsesquioxanes used for the manufacture of highly filled thermo- and fire-resistant polymer composite materials has been presented.